Pretreatment of empty palm fruit bunch for production of chemicals via catalytic pyrolysis - Missona, Mailin (Elsevier BV, 2009)
The effect of chemical pretreatments using NaOH, H2O2, and Ca(OH)2 on Empty Palm Fruit Bunches (EPFB) to degrade EPFB lignin before pyrolyis was investigated. Spectrophotometer analysis proved consecutive addition of NaOH and H2O2 decomposed almost 100% of EPFB lignin compared to 44% for the Ca(OH)2, H2O2 system while NaOH and Ca(OH)2 used exclusively could not alter lignin much. Next, the pretreated EPFB was catalytically pyrolyzed. Experimental results indicated the phenolic yields over Al-MCM-41 and HZSM-5 catalysts were 90 wt% and 80 wt%, respectively compared to 67 wt% yield for the untreated sample under the same set of conditions. Meanwhile, the experiments with HY zeolite yielded 70 wt% phenols.